Sinodalidade e missão: O legado do Concílio de Jerusalém - Barro, Jorge Henrique (Revista Eclesiástica Brasileira, 2025)
Este artigo explora a sinodalidade como prática e conceito fundamental para a Igreja contemporânea, utilizando o Concílio de Jerusalém, narrado em Atos 15, como paradigma histórico e teológico. Inicialmente, analisa o significado da sinodalidade no contexto católico e protestante, destacando sua aplicação como um caminho de comunhão e discernimento. O Concílio de Jerusalém é apresentado como modelo de unidade em meio à diversidade, evidenciando práticas de escuta mútua, dependência do Espírito Santo e equilíbrio entre liberdade cristã e sensibilidade cultural. O estudo também aborda o impacto prático da decisão tomada pelo Concílio, que promoveu alegria, paz e fortalecimento espiritual nas comunidades cristãs. Por fim, reflete sobre as implicações da experiência para a prática sinodal na Igreja contemporânea, destacando cinco aspectos principais: escuta ativa, dependência do Espírito Santo, unidade na diversidade, testemunho público e saúde espiritual. Abstract: This article examines synodality as a fundamental practice and concept for the contemporary Church, using the Jerusalem Council, narrated in Acts 15, as a historical and theological paradigm. It begins by analyzing the meaning of synodality within Catholic and Protestant contexts, emphasizing its role as a path of communion and discernment. The Jerusalem Council is presented as a model of unity amidst diversity, showcasing practices of mutual listening, reliance on the Holy Spirit, and a balance between Christian freedom and cultural sensitivity. The practical impact of the Council’s decision is also discussed, highlighting the resulting joy, peace, and spiritual strengthening in Christian communities. Finally, it reflects on the implications of this experience for the contemporary Church’s synodal practice, emphasizing five key aspects: active listening, dependence on the Holy Spirit, unity in diversity, public witness, and the spiritual health of the Church. Keywords: Synodality; Jerusalem Council; Christian Unity; Mutual Listening; Inclusive Mission.